Hirshfeld surface, crystal structure and spectroscopic characterization of (E)-4-(diethylamino)-2-((4-phenoxyphenylimino)methyl)phenol with DFT studies - Kanmazalp, Sibel Demir; Macit, Mustafa; Dege, Necmi (Elsevier, 2019)
The '(E)-4-(diethylamino)-2-((4-phenoxyphenylimino)methyl)phenol (DPMP)' compound, C23H24N2O2 is synthesized and verified by single crystal X-ray diffraction. Additionally, the molecule is designated by UV-Vis and FT-IR spectroscopies and computed in ground state by Density Functional Theory (DFT/B3LYP) using 6-311 + G (d, p) basis set. The optimized geometric parameters and vibrational frequencies indicate good consistency with the experimental data. Hirshfeld surface analyses (d(norm) surfaces and two-dimensional fingerprint plots) for DPMP are presented and discussed. Natural Bond Orbital (NBO) analysis is conducted to explore the interactions and charge transfers among different orbitals and lone pairs taking place within the titled compound. Molecular Electrostatic Potential (MEP) and the electronic features such as HOMO and LUMO energy gap illustrate the chemical activity of the DPMP. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Schiff base; Hirshfeld surface; X-ray; FT-IR; UV-Vis; NBO